Synthesis of porous MnCo2O4 microspheres with yolk–shell structure induced by concentration gradient and the effect on their performance in electrochemical energy storage. Issue 13 (26th January 2016) - Huang, Guoyong; Xu, Shengming; Yang, Yue; Sun, Hongyu; Xu, Zhenghe
Abstract : In this study, novel spherical yolk–shell MnCo2 O4 powders with concentration gradient have been synthesized. Abstract : In this study, novel spherical yolk–shell MnCo2 O4 powders with concentration gradient have been synthesized. The porous microspheres with yolk–shell structure (2.00–3.00 μm in average diameter, ∼200 nm in thickness of shell) are built up by irregular nanoparticles attached to each other. It is shown that the formation of yolk–shell structure may be induced by the core–shell concentration gradient. And the Co : Mn atomic ratios of core and shell are about 1.65 : 1 and 2.61 : 1, respectively. Interestingly, a similar uniform spherical MnCo2 O4 without yolk–shell structure and concentration gradient prepared as a contrast, the superior electrochemical performance of the former by using in Li-ion batteries and supercapacitors has been proved including higher initial discharge capacity (1445.1 mA h g −1 at 0.2 A g −1 ) and initial specific capacitance (761.3 F g −1 at 2 A g −1 ), and more advanced capacity retention (∼860.0 mA h g −1 after 40 cycles at 0.2 A g −1, and ∼330.0 F g −1 after 3000 cycles at 12 A g −1 ).